Study of the Effect of Quenching and Tempering Modes on the Strength Level of Alloyed Structural Steels Used to Produce Fasteners - Alexander Zaitsev; Anton Koldaev; Alexey Stepanov; Nataliya Arutyunyan; Alexey Stolyarov; Mariya Zaytseva; Dmitrii Konstantinov (Metals, 2022)
The development of high-strength fasteners is required due to the modern trend of reducing the weight of engineering structures. At present, structural bolts of property classes 8.8–10.9 are widely used, and higher-strength bolts of property classes 12.9 and 14.9 are being developed. In this paper, we analyzed the possibilities and conditions for manufacturing fasteners of different strength categories from steels of seven grades, containing and not containing boron. The necessary corresponding temperature ranges of processing are determined based on the study of hot-rolled round steel. Tensile strength, yield strength, relative elongation, reduction in area, and Vickers microhardness were measured. An analysis was made of the hardenability and the influence of the holding time during tempering on the mechanical properties of the considered round steel. Using the method of scanning electron microscopy, the effect of carbide precipitation during tempering on the mechanical properties of fasteners was established.